The internationalisation of higher education: a networking based conceptual framework - Munusamy, M.Miandy; Hashim, Azirah (AEI Insights, 2021)
Internationalisation is an important worldwide phenomenon and a major trend in higher education. It is also one of the ways nations react to the impact of globalisation. There are multiple rationales that encourage various national governments, higher education institutions, international organisations and the private sector to proactively engage in educational services across national borders. Internationalisation theories have primarily focused on the internationalisation process in the business and economic dimensions, but since 1980s, it has influenced the structure of education and higher education systems. The network approach emphasises the benefits of developing long-term interactions with foreign markets, institutions and individuals. Networking also provides an important motivation for nations and higher education institutions to enrich international activities and expand their landscape, share best practices as well as transfer knowledge and balance risks. The study explores the Uppsala and network theories of internationalisation and its feasibility for examining networking in the internationalisation of higher education. It provides new insights into how the network model of internationalisation allows the influence of external actors or organisations to impact on the process of internationalisation of higher education. A conceptual framework on networking perspectives in internationalisation, which has the potential to contribute towards achieving internationalisation goals and the enhancing quality of higher education is proposed.